THE SIGNIFICANCE OF AXILLARY BLOCK IN UPPER ARM AMPUTATION IN A PATIENT WITH SERIOUS COMORBIDITIES: A CASE REPORT - Nikolic, Aleksandar; Damnjanovic, Zoran; Stepanovic, Nemanja; Damnjanovic, Goran; Ristic, Uros; Vasilijic, Milena; Stosic, Marija; Zivadinovic, Jelena; Stojanovic, Marko; Rancic, Dejan; Djordjevic, Miodrag (Acta medicae Medianae, 2025)
Surgical management is sometimes the only viable treatment option for patients with peripheral arterial occlusive disease. However, performing surgery under general endotracheal anesthesia in patients with hemodynamic and respiratory instability poses a significant challenge. In such cases, neuraxial blocks may provide a safer alternative. An 80-year-old male patient was urgently admitted to the Department of Internal Medicine at the Military Hospital Niš due to difficulty breathing and a livid discoloration of the left hand and forearm. Carpal pulses were absent, and the patient had experienced loss of movement and sensation in the hand for several days. Clinical examination and Multislice computed tomographc angiography of the pulmonary and major arteries of the left arm confirmed a diagnosis of pulmonary embolism and occlusion of the subclavian and brachial arteries. After evaluating the patient’s condition, the anesthesiologist opted for a neuraxial block instead of general endotracheal anesthesia. Avoiding general endotracheal anesthesia and utilizing neuraxial blocks could minimize the possibility of adverse events in high-risk patients.